The borage family (Boraginaceae s.str.): A revised infrafamilial classification based on new phylogenetic evidence, with emphasis on the placement of some enigmatic genera. Issue 3 (1st June 2016) - Chacón, Juliana; Luebert, Federico; Hilger, Hartmut H.; Ovchinnikova, Svetlana; Selvi, Federico; Cecchi, Lorenzo; Guilliams, C. Matt; Hasenstab-Lehman, Kristen; Sutorý, Karel; Simpson, Michael G.; Weigend, Maximilian
Abstract: Boraginaceae s.str. is a subcosmopolitan family of 1600 to 1700 species in around 90 genera, and recent phylogenetic studies indicate that the infrafamilial classification as currently used is highly obsolete. The present study addresses the relationships of the major clades in Boraginaceae s.str. with an emphasis on monophyly of, and relationships between previously recognized clades and the position of various unplaced genera such as Afrotysonia, Anoplocaryum, Brachybotrys, Chionocharis, Craniospermum, Thyrocarpus, and Trigonocaryum using three plastid markers and a taxon sampling with four outgroup and 170 ingroup species from 73 genera. The phylogeny shows high statistical support for most nodes on the backbone and within individual clades. Echiochileae are confirmed as sister to the remainder of Boraginaceae s.str., which, in turn, fall into two well‐supported clades, the Boragineae + Lithospermeae and the Cynoglosseae s.l. The latter is highly resolved and includes the Lasiocaryum ‐clade ( Chionocharis, Lasiocaryum, Microcaryum ) and the Trichodesmeae ( Caccinia, Trichodesma ) as sister to the remainder of the group. Rochelieae (formerly the Eritrichieae s.str., also including Eritrichium, Hackelia, and Lappula ) form a poorly supported polytomy together with the Mertensia ‐clade (also including Anoplocaryum, Asperugo, and Memoremea ) and the Omphalodes ‐clade. The enigmatic genus Craniospermum (Craniospermeae) is sister to an expanded Myosotideae (also including Brachybotrys, Decalepidanthus, Trigonocaryum, and Trigonotis ) and these two clades are in turn sister to the Core‐Cynoglosseae, in which Afrotysonia glochidiata and Thyrocarpus sampsonii are included. Core‐Cynoglosseae again fall into two pairs of well‐supported subclades. The majority of generic placements are now resolved satisfactorily and the remaining phylogenetic questions can be clearly delimited. Based on the extensive phylogenetic data now available we propose a new infrafamilial classification into three subfamilies and 11 tribes, representing a consensus among the participating authors, according to which major clades are renamed.